Cervical paraspinal muscle fatty degeneration and postoperative kyphosis after cervical laminoplasty - Karan Joseph; Miguel A. Ruiz-Cardozo; Karma A. Barot; Gabriel Trevino; Tim T. Bui; Samuel J. Vogl; Samuel N. Brehm; Matthew J. Strok; Salim Yakdan; Michael R. Kann; Sofia Lopez-Alviar; Alexander T. Yahanda; et al. (Journal of Craniovertebral Junction and Spine)
Background: Sarcopenia, a manifestation of frailty characterized by muscle loss, is associated with adverse postoperative events in spinal patients. Its role in postlaminoplasty kyphotic deformities (PKDs) remains unknown. Objective: This study evaluates the relationship between paraspinal muscle sarcopenia and PKD using qualitative and quantitative methods. Materials and Methods: A retrospective review was conducted on cervical myelopathy patients treated with laminoplasty between January 2019 and January 2022 at a tertiary care center. Inclusion criteria included pre- and 1-year postoperative X-rays and magnetic resonance imaging within 6 months presurgery. PKD was defined as loss of cervical lordosis greater than −10° based on the C2-7 Cobb angle. Fatty infiltration was evaluated using Goutallier classification and voxel quantification. Results: Among 44 patients, 4 developed PKD. Qualitatively, 32 patients were classified as Goutallier 0–1.5, 6 were Goutallier 1.5–2.5, and 6 Goutallier 2.5–4. There is a significant association between the Goutallier grade and PKD occurrence after 1 year (P = 0.00085). Quantitatively, the average fatty infiltration percentage for the kyphotic patients was 23.3% ± 5.81% versus 13.8% ± 9.83% for nonkyphotic patients. A significant association was found between the percentage of fatty infiltration and the PKD after 1 year (P = 0.045). The optimal fat cutoff between kyphotic and nonkyphotic patients was 23% (P = 0.056). Conclusions: The present study demonstrated that patients with higher degree of fatty infiltration were associated with PKD. Based on our results, patients with increased cervical paraspinal degeneration may have increased risk of developing PKD. With this information, surgeons may be better equipped to predict the risk of PKD.